The scope for adaptive capacity in emergency departments: modelling performance constraints using control task analysis and social organisational cooperation analysis. Issue 3 (4th March 2022) - Austin, E.; Blakely, B.; Salmon, P.; Braithwaite, J.; Clay-Williams, R.
Abstract: Patient flow between the emergency department (ED) and hospital wards becomes problematic when bed availability is limited. To better understand the constraints that shape patient flow and everyday work in the ED, we applied Control Task Analysis (i.e. Contextual Activities Template, CAT) and Social Organisational Cooperation Analysis (SOCA) phases from the Cognitive Work Analysis framework to identify ways in which to optimise patient flow. The model and analysis were created through observations in the ED of clinicians (e.g. nurses, doctors), and professional staff (e.g. ward personnel, clerks). The CAT and SOCA-CAT models illustrate workspaces, patient journey phases, and patient volume within the department that are heavily loaded with tasks and human and non-human agents performing these tasks, while others are underutilised. The findings suggest that an ED's adaptive capacity could be strengthened through the integration of additional human and non-human agents allowing the redistribution of clinical and non-clinical tasks. Practitioner Summary: Workflow in EDs is constrained by uneven geographical distribution of activities, insufficient adaptive support during critical patient journey phases and periods of high patient volume. Adaptive capacity could be strengthened by additional human and non-human agents in combination with a redistribution of tasks, supporting seamless successful structural and behavioural adaptation in ED.